Lipid metabolism in astrocytic structure and function. (April 2021) - Lee, James AK; Hall, Benjamin; Allsop, Jessica; Alqarni, Razan; Allen, Scott P.
Abstract: Astrocytes are the most abundant glial cell in the central nervous system and are involved in multiple processes including metabolic homeostasis, blood brain barrier regulation and neuronal crosstalk. Astrocytes are the main storage point of glycogen in the brain and it is well established that astrocyte uptake of glutamate and release of lactate prevents neuronal excitability and supports neuronal metabolic function. However, the role of lipid metabolism in astrocytes in relation to neuronal support has been until recently, unclear. Lipids play a fundamental role in astrocyte function, including energy generation, membrane fluidity and cell to cell signaling. There is now emerging evidence that astrocyte storage of lipids in droplets has a crucial physiological and protective role in the central nervous system. This pathway links β-oxidation in astrocytes to inflammation, signalling, oxidative stress and mitochondrial energy generation in neurons. Disruption in lipid metabolism, structure and signalling in astrocytes can lead to pathogenic mechanisms associated with a range of neurological disorders.